Treating depression in diabetic patients: Latihan pasrah diri (LPD) revisited - Agus Siswanto; Arief Kurniawan Siregar; Ahmad Husain Asdie (Faculty of Medicine Universitas Gadjah Mada, 2016)
The condition accompanying depression will always be progressing into poor prognosis if the depression itself is not recognized and treated properly. Among diabetic patients, depression was associated with increased mortality and poor quality of life . It was observed that diabetes and depression has a bidirectional relationship, where the clinical course of both conditions are affecting each other. Despite the effectiveness of psychological and psychopharmacological interventions in treating depressive symptoms in diabetic patients, the effect of such interventions on glycemic control is still inconsistent. Complementary alternative medicine (CAM) alone or in combination with standard medical treatment, targeting both depression and diabetes, appears to be promising. Latihan Pasrah Diri (LPD) has been recognized as a type of relaxation technique under CAM. It is initially directed to provide adequate relieve of depression using both religious and relaxative approach. Among patients with comorbid diabetes and depression, this approach has long been known and utilized over the counter, but its formal practice is seldom advocated, whereas, many clinical trials has been conducted locally to reveal its potential use. Combined with standard therapy, LPD is expected to show its beneficial effects.